2014
DOI: 10.4103/1947-2714.131243
|View full text |Cite
|
Sign up to set email alerts
|

Is Dementia Differentially Distributed? A Study on the Prevalence of Dementia in Migrant, Urban, Rural, and Tribal Elderly Population of Himalayan Region in Northern India

Abstract: Background:Throughout the world, a large number of surveys have been carried out to find the prevalence of dementia with variable results.Aims:This study was to generate data on the prevalence of dementia and to generate a hypothesis on the differential distribution across populations.Materials and Methods:Four settings identified for the purpose of this study included a migrant, urban, rural, and tribal. The study was conducted in two phases: 1) A screening phase and 2) a clinical phase, on 2,000 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 14 publications
2
45
1
Order By: Relevance
“…The prevalence of Zhejiang province in our study was 13%, higher than the national survey conducted among Chinese people aged 65 and older (5.14%) [2, 26]. In the investigation, we also found that few of the dementia patients were treated regularly with anti-dementia drugs, and none of them received cognitive rehabilitation therapies.…”
Section: Discussioncontrasting
confidence: 51%
“…The prevalence of Zhejiang province in our study was 13%, higher than the national survey conducted among Chinese people aged 65 and older (5.14%) [2, 26]. In the investigation, we also found that few of the dementia patients were treated regularly with anti-dementia drugs, and none of them received cognitive rehabilitation therapies.…”
Section: Discussioncontrasting
confidence: 51%
“…There are limited studies evaluating the influence of within-country migration (i.e., change of residential status). Only 2 studies based on small, regional samples compared the prevalence of cognitive impairment between rural residents, urban residents, and migrants [7, 8]. The results from these two studies were inconclusive – one study showed a higher prevalence of cognitive impairment in urban than in rural and migrant populations [8], while the other showed no statistically significant differences in the prevalence of cognitive impairment among the 3 groups [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in cognition were not fully explained by sex and geographic location. Other factors, such as within-country migration, could impact later-life cognitive function [7-9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on estimating the prevalence of dementia in different settings reveals that, the studies are generally conducted using a two phase strategy: (1) A screening phase and (2) a clinical phase. [3][4][5] The screening is generally conducted by using a screener like the MMSE or its modified versions and identifying suspects for clinical evaluation. The authors could have similarly identified suspects for clinical evaluation (for dementia), after administering the IHDS as a screening tool.…”
Section: Use Of International Hiv Dementia Scale In Assessment Of Neumentioning
confidence: 99%